EVALUASI PENGELOLAAN PEMBIYAAN PENDIDIKAN - Aprilliantoni, Aprilliantoni; Listiowati, Listiowati; Sidqia, Fanny (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2025)
This study aims to evaluate the management of education funds in Indonesia, with a focus on the effectiveness, efficiency, and accountability of the use of educational funds. The method used in this study is a qualitative descriptive method, which includes the analysis of education budget data, interviews with education finance officers, and office studies related to the allocation of education and the use of funds. The results of the study show that, although the allocation for educational facilities is relatively large, its management still faces issues such as uneven distribution of funds, low transparency, and high dependence on community funds. This study recommends improvements in budget planning that are more needs-based, more transparent, and diversifying funding sources to improve the quality and equity of education across Indonesia.